KEBERADAAN FORUM KOORDINASI KEPEMIMPINAN (FORKOPIMDA) PADA SISTEM PEMERINTAH DAERAH DI KABUPATEN TANAH DATAR - Kuntjoro, Bagus Tri (UNES Law Review, 2020)
The Regional Leadership Coordination Forum, hereinafter referred to as Forkopimda, is a forum used to discuss the implementation of general government affairs. In accordance with article 26 of Law No. 23 of 2014 stated that the District Forkopimda was led by the Regent with members including the DPRD Chairperson, the Police Chief, the Prosecutor's Office and the territorial leadership of the TNI in the regions. The issues raised as the subject of this research study are: First, What is the existence of the Regional Leadership Coordination Forum (FORKOPIMDA) in the regional government system? Second, how is the existence of the Regional Leadership Coordination Forum (FORKOPIMDA) in order to maintain stability in the region in terms of ideology, politics, economy, social culture, and defense and security. This research is an analytical descriptive research with normative juridical approach supported by empirical juridical research. The data used are secondary and primary data collected through literature studies and interviews, analyzed qualitatively to get answers about the existence of the Regional Leadership Coordination Forum in the government system in Tanah Datar District which is the study of this study. Based on the results of research and discussion, it can be concluded that the Regional Leadership Coordination Forum (Forkopimda) Tanah District has the role and duty of fostering, maintaining peace and order of the community against the possibility of the threat of national stability and stability of Tanah Datar regency carried out through FORKOPIMDA meetings and activities field observations both periodically and incidentally by looking at events or problems that arise in the Tanah Datar District. While the existence of the Regional Leadership Coordination Forum (Forkopimda) of Tanah Datar District was very much felt and assisted the Tanah Datar Regency Government in creating security, order and legal certainty in community life and ensuring the implementation of development in Tanah Datar District which had the slogan "Adat Basandi Syarak, Syarak Basandi Kitabbullah "which in turn can improve the welfare of the people of Tanah Datar District.